(untitled) (Global Journal of Science Frontier Research, 2012)
This study examined the effect of social network on microcredit access among grains sellers in Ibadan metropolis, Oyo State, Nigeria. Multistage stratified random sampling procedure was employed to collect data from 150 grains sellers from three randomly selected local government areas (LGAs) in Ibadan. Primary data were collected using a well structured questionnaire. The data were analyzed using descriptive statistics and probit regression analysis and 2-stage least square. The result showed banks and cooperatives as two main sources of credit for the grain sellers and majority of the grain sellers reported that local level institutions (LLIs) facilitate their access to credit. The result of probit regression showed that age, age squared, marital status and religion; social capital index, cash contribution, labour contribution index and decision making index significantly affect microcredit access. It revealed that the higher the cash and labour contribution of grain seller to their associations the more access to microcredit. The result of bi-causal relationship showed that social capital was truly exogenous to grain seller’s access to microcredit with no reverse causality. The study concluded that social capital positively affected credit access.